Effects of boysenberry on postprandial energy metabolism in healthy adults: A randomized controlled crossover trial - Ryo Furuuchi; Satoshi Kato; Daisuke Maejima; Tatsuro Amano; Ippei Shimizu; Tohru Minamino (PLoS ONE, 2025)
Brown adipose tissue (BAT) is essential for thermoregulation and energy metabolism, converting fatty acids into thermal energy in response to cold exposure and dietary intake, thereby contributing to both cold-induced thermogenesis and diet-induced thermogenesis (DIT). Our previous research suggests that boysenberry anthocyanins (BoyACs) may activate BAT under cold conditions, and we hypothesized that BoyACs could also influence DIT through the activation of BAT. This pilot randomized, double-blind crossover trial aimed to evaluate the effects of daily intake of BoyACs on DIT in healthy adults (registration number: UMIN000047413). Twenty-two participants consumed either a boysenberry juice (BoyJ) beverage containing 61.0 mg of BoyACs or a placebo beverage daily for four weeks, with a four-week washout period separating the two interventions. Three participants withdrew during the trial, resulting in data from 19 participants being analyzed. Results showed no significant changes in DIT, defined as increase in postprandial energy expenditure, or skin temperature of BAT regions. However, a significant increase in postprandial fat oxidation was observed. No significant differences were observed in other outcomes. These results suggest that BoyJ intake does not significantly affect postprandial energy expenditure but may influence substrate utilization to promote fat oxidation. Further studies focusing on substrate utilization, particularly fat oxidation, as the primary outcome are necessary to confirm these results and fully understand the implications of BoyJ intake on energy metabolism.